CFD-based simulation of the hydrodynamics of steady-state gas–liquid in ultrasonically oscillating microreactors - Guangyong Huang; Xiangfu Wei; Lin Lin; Cuimin Sun; Xuejun Liu; Jiapeng Chen; Haojie Dang; Rongxing Zhu; Hui You (AIP Advances)
Ultrasound-driven microbubble oscillation in a microchannel is commonly used in mixing and mass transfer, and its steady-state mechanisms are complex. This study proposes an acoustic streaming steady-state model for the oscillation between two microbubbles driven by ultrasound in a square microchannel (150 × 150 μm2). The breathing mode and shape oscillation mode of the bubble cap were experimentally analyzed at an ultrasound frequency of 97.5 kHz, and the flow patterns of liquid slugs were found to be completely opposite. A two-dimensional numerical model of the two microbubble oscillations was developed from a new perspective of steady state. The correctness of the model was verified by comparing the 2 μm diameter polystyrene tracer flow field with the simulation results. The steady-state flow field was analyzed in terms of ultrasound amplitude, shape, size, and liquid property parameters. The streaming velocity was found to be directly proportional to the square of the microbubble amplitude. When the bubble cap became more hydrophilic and sharper, the mixing effect improved. In particular, it was found that the microbubbles had the most intense disturbance to the fluid when the distance between the two microbubbles was twice the channel width.